76 PHENOTYPIC AND GENETIC CHARACTERIZATION OF A COMMON DENTOFACIAL DEFORMITY: MANDIBULAR PROGNATHISM. (1st March 2006) - Frazier-Bowers, S. A.; Bui, C.; King, T. M.; Proffit, W. R.
Abstract : Although substantial evidence has supported the role of heredity in Class III dentofacial deformity (mandibular prognathism), the relative contribution of genetic and environmental factors that led to this dentofacial problem, however, continues to be debated. The objective of this study is to elucidate the role of genetics in the development of the Class III trait. We therefore performed a detailed phenotypic characterization of both isolated and familial cases of Class III dentofacial deformity to address the fundamental hypothesis that the Class III trait is an inherited trait with distinctly segregating subphenotypes. We further propose to categorize individuals based on these subphenotypes that can ultimately be correlated with specific haplotypes. It should be possible to eventually understand the contribution of genetic factors in the various expressions of Class III dentofacial problems and to apply this knowledge to improved treatment approaches. To date 15 families with multiple affected individuals have been identified within the existing database of the Dentofacial Clinic at the University of North Carolina through which surgical patients are followed and through the records of the graduate orthodontic clinic and faculty practice. Cluster and principal components analyses were performed using cephalometric variables to compare familial and isolated Class III individuals. Finally, a genome-wide scan followed by linkage analysis was conducted to identify the chromosomal locus of the Class III trait for four families with significant power. The results indicated that there are five clusters, from 309 individuals, representing clinically distinct phenotypes. A pedigree "analysis by inspection" revealed that the broad Class III phenotype is inherited as an autosomal dominant trait in 15 families analyzed. Linkage analysis reveals a locus suggestive of linkage with the Class III trait. We therefore conclude that the Class III dentofacial deformity is largely under strict genetic control and is made up of distinct subphenotypes.